Handbuch der kontrastiven Alphabetisierung - Marschke, Britta; SpringerLink (Online service) (Berlin : Erich Schmidt Verlag GmbH & Co. KG : Imprint: Erich Schmidt Verlag GmbH & Co. KG, 2022)
Dies ist ein Open-Access-Buch.
Keywords: Language and languages -- Study and teaching; Philology; Germanic languages; Language Education; Philology; Germanic Languages